Self-employment and health inequality of migrant workers - Deshui Zhou; Xin Wen (BMC Health Services Research, 2022)
Abstract Background Self-employment is one of the most common forms of employment for migrant workers in China. However, migrant workers’ lifestyle and behavior, as well as health disparities among them, would be impacted by self-employment. This research aims to explore the mechanism and group differences of the effect of self-employment on health inequality among Chinese migrant workers. Materials and methods To explore the effect of self-employment on health inequalities among migrant workers, this research uses the data from the 2018 China Migrant Workers Dynamic Monitoring Survey, and the RIF-I-OLS decomposition method. Results We find that self-employment will reduce the health inequality of Chinese migrant workers significantly, especially among migrant workers with low education, low income, and low social integration. A further examination reveals that self-employment can directly promote the self-rated health of migrant workers. Additionally, it indirectly alleviates the health inequality among migrant workers by mediating effect of expanding access to public welfare, such as by establishing health records and strengthening health education. Conclusion The government should permit and encourage migrant workers to engage in self-employment. It is necessary to provide public services such as health education, health records, and health rights for migrant workers, and focus on the employment of migrant workers in city, especially those with low income and low education. we believe that measures should be taken to enhance migrant workers’ sense of belonging in urban China Only on this basis can health inequality among migrant workers be truly reduced.